The Influence of Recruitment and Work Motivation on Employee Productivity with Competence as a Mediating Variable: A Literature Review - Faizal Rachman; Hapzi Ali (Siber Nusantara of Economic and Finance Review, 2025)
Employee productivity is a primary indicator of organizational success in achieving strategic objectives. Numerous studies indicate that productivity is influenced by the quality of recruitment and the level of employees’ work motivation. However, this relationship is not always direct and is often mediated by employee competence. This study aims to comprehensively examine the relationships among recruitment (X1), work motivation (X2), competence (M), and employee productivity (Y) through a systematic literature review approach. Data were obtained from nationally accredited journals indexed in SINTA and reputable international journals published over the past ten years. The findings demonstrate that recruitment and work motivation have a significant effect on employee productivity, both directly and indirectly through competence. These results emphasize the importance of competence-based human resource management as a strategic approach to enhancing organizational productivity.